1993
DOI: 10.1577/1548-8675(1993)013<0346:eodtes>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deflating the Expanded Swim Bladder on Survival of Burbot

Abstract: We found no evidence that deflating the expanded swim bladder of burbot Lota lota affected survival. In a mark-recapture study of the species in Green Bay, Lake Michigan, many burbot caught from depths greater than 10 m floated at the surface when tagged and released because of expanded swim bladders. We deflated the swim bladders by forcing a hollow needle through the body wall to puncture the expanded organ, and we conducted two experiments to assess the effect of our procedures on survival. In one experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 3 publications
1
42
0
Order By: Relevance
“…Similar to past studies on gas bladder deflation, we found no mortality in fish with barotrauma that were subjected to fizzing (e.g., Bruesewitz et al, 1993;Shasteen and Sheehan, 1997). Other studies recorded mortality but found no significant difference between deflated fish and non-deflated fish (e.g., Lee, 1992;Gitschlag and Renaud, 1994), and some studies have shown a positive effect of artificial swim bladder deflation on yellow perch (Keniry et al, 1996), black sea bass and vermillion snapper (Collins et al, 1999).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Similar to past studies on gas bladder deflation, we found no mortality in fish with barotrauma that were subjected to fizzing (e.g., Bruesewitz et al, 1993;Shasteen and Sheehan, 1997). Other studies recorded mortality but found no significant difference between deflated fish and non-deflated fish (e.g., Lee, 1992;Gitschlag and Renaud, 1994), and some studies have shown a positive effect of artificial swim bladder deflation on yellow perch (Keniry et al, 1996), black sea bass and vermillion snapper (Collins et al, 1999).…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, we recommend hypodermic needle as its puncture would heal the fastest noted by Shasteen and Sheehan (1997) who reported swim bladders healed slower for larger incisions (0.5 cm) made in the swim bladder of largemouth bass than for needle punctures (17 h). Other observations demonstrated swim bladders healed within 4 days for red snapper and red grouper (Burns and Restrepo, 2002), and healed relatively quickly in burbot (within 8 weeks; Bruesewitz et al, 1993). These findings confirm that fizzing is not unfavourable to barotrauma fish; however, accidental punctures of other organs can have adverse effects (as reviewed by Kerr, 2001).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Two studies found no effect on survivorship. Deflation had no detrimental effect on burbot Lota lota (Bruesewitz et al, 1993) and increased survival of largemouth bass (Feathers and Knable, 1983), black sea bass (Collins et al, 1999), and yellow perch (Keniry et al, 1996). Survival of vermilion snapper increased in one study (Fable, 1994), but not significantly in another (Collins et al, 1999).…”
Section: Ventingmentioning
confidence: 90%